Nonlinear 6-DOF Dynamic Simulations for Center-Articulated Vehicles with combined CG*. Issue 14 (2022) - Badar, Tabish; Backman, Juha; Tariq, Usama; Visala, Arto
Abstract: This study highlights a combined center of gravity (CG) approach to model the comprehensive dynamics of the ground vehicles with articulated steering using solely six degrees of freedom (6-DOF). It is the case with an articulated vehicle that its CG shifts laterally towards the center of rotation during a turn. Thus, the idea is to compute the combined CG position of the multi-body articulated vehicle, which leads to the correction of the moment arms and body inertias about the updated CG position in the dynamic equations. Hence, the body forces and moments are computed with respect to the corrected CG position. In addition, the paper illustrates mathematical modeling of the center-articulated steering mechanism for the ground vehicle while restricting its operation to the primary handling regime. Overall, the draft presents the design of a nonlinear 6-DOF simulation for a load-haul-dump (LHD) type of articulated vehicle with a traveling CG. The simulation data is presented from one simulation run, where the critical results are analyzed. The obtained results signify the simplicity in using a combined CG to represent the vehicle dynamics.